A COMPARATIVE STUDY OF CONVENTIONAL BONDS AND ISLAMIC SUKUK, AND THEIR USE OF THE TRUST INSTRUMENT - Chambers, Joseph Anthony (Kent Law Review, 2017)
The English trust form has been an invaluable tool in the growth and development of capital markets, assisting in the smooth running of the bond markets in a way which is seemingly unattainable through contract law alone. During the course of the last few years, however, modern western finance has begun to experiment with, and embrace, a new legal instrument: the Islamic Sukuk. Similar to bonds in their employment of the trust form, the Sukuk is growing to be an essential tool in modern finance, providing western business with an opportunity to tap a previously restricted source of funding. Since the introduction of the instrument its’ use has continued to grow, with many city law firms now having specialist Islamic Finance teams to tackle the unique questions and hurdles that the integration of sukuk into the western financial system inevitably creates. This article examines the use of the trust form by both traditional bonds, and the Islamic sukuk, to ascertain why the trust is so valuable, and begins to assess what advantages and disadvantages may arise from the more common use of the sukuk in our western financial system.